DATA ENCRYPTION ALGORITHM AES BY USING BLOCKCHAIN TECHNOLOGY: A REVIEW - Hidayat, Taufik; Mahardiko, Rahutomo (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
Blockchain is used as encryption algorithm in cryptocurrency, but less researches are found to study blockchain for data encryption. Data encryption is needed to protect the data from data theft. We know about data encryption, there are RSA, LEAP, AES, and other algorithms. This research proposed a review in AES algorithm for data encryption within blockchain technology. The research process is followed by determining library, then creating relevant questions and criteria. For good opportunity in the future, this paper generated suggestions and opportunities so that better research can be established in data encryption.